Actinobacteria from Mangrove Rhizosphere as a Source of Biocontrol Agents to Support Sustainable Agriculture - Sakaroni, Rubiyatna; Kusuma, Anindita Suliya Hangesti Mandra; Adawiyah, Marosa Robi'atul (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2025)
Mangrove ecosystems harbor diverse microorganisms with important ecological and biotechnological roles. Actinobacteria, in particular, are well known as producers of bioactive compounds and potential biocontrol agents against plant pathogens, making their exploration relevant for sustainable agriculture. This study aimed to isolate and characterize Actinobacteria from the rhizosphere of mangroves in Bagek Kembar, West Lombok, and to evaluate their antagonistic potential against Ralstonia solanaciearum, plant disease agent. Soil samples were collected using a quadrant method, while environmental parameters such as pH, temperature, humidity, and salinity were measured to assess habitat suitability. Actinobacteria were isolated and identified through Gram staining and morphological observation, their abundance was calculated using the Total Plate Count method, and antagonistic activity was tested using the agar well diffusion assay. The results showed that soil pH was relatively neutral, with temperature and salinity suitable for Actinobacteria growth. Five isolates (ACT R1–R5) were obtained, all Gram-positive with filamentous hyphae-like morphology. Total Plate Count analysis indicated high abundance (3.2 × 105), although the diversity of isolates recovered was relatively low. Antagonistic assays revealed that ACT R2 and ACT R4 moderate inhibitory effect, and ACT R1, ACT R3, and ACT R5 weak. Overall, these findings demonstrate that mangrove rhizospheres in West Lombok are a promising source of Actinobacteria with significant potential as environmentally friendly biocontrol agents